Mindfulness and self-affirmation interventions for orphaned children: differential effects on psychological well-being - Pedi Kurniawan; Tjhia Kie Khiong; Budi Utomo (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study investigates the effects of mindfulness practice and self-affirmation on the psychological well-being of orphaned children at the Buddhayana Vidyalaya Foundation in Bandar Lampung, Indonesia. A quasi-experimental design was employed with 62 participants. Due to dormitory-based institutional arrangements, female children (n = 32) were assigned to the experimental group receiving mindfulness and self-affirmation interventions, while male children (n = 30) served as the control group. This non-equivalent grouping should be interpreted cautiously because gender differences may confound the treatment effects. The intervention was delivered in six online sessions via Zoom. Simple regression analysis showed that mindfulness (R² = 0.347, p < 0.001) and self-affirmation (R² = 0.405, p < 0.001) were individually associated with psychological well-being. However, in the multiple regression model, only self-affirmation remained a significant predictor (β = 0.587, p = 0.035), whereas mindfulness was not significant (p = 0.168). Although the model explained 44.5% of the variance, the practical impact was minimal (Cohen’s d = 0.049). The limited effect may be related to the short intervention duration, online delivery, and varying participant engagement.